Determinants of Low Birth Weight Incidence at Padangsidimpuan City Hospital in 2025 - Hafni, Seri; Harahap, Meilani; Hasibuan, Darma Afni; Siregar, Rahmi Wahida; Putri, Yolanda; Rangkuti, Layla Fadhilah (International Journal of Public Health Excellence (IJPHE), 2025)
The infant mortality rate in Indonesia based on the 2012 Indonesian Demographic and Health Survey (SDKI) was 32 per 1,000 live births and the Neonatal Mortality Rate (AKN) in 2012 was 19 per 1,000 live births.This research is a quantitative analytical study with a case-control design using secondary data from medical record. The population size in this study was 104 mothers who gave birth with low birth weight (LBW).Padangsidimpuan City Hospital in 2025 period from January to September 2025. Researchers can draw the following conclusions 51% of mothers who gave birth to LBW were at risk, 79.8% had low education, 78.8% had high risk parity, 41.3% were working mothers and 65.4% experienced complications during pregnancy. Factors related to the incidence of LBW are maternal age (p value 0.000), education (p value 0.002), parity (p value 0.002) and pregnancy complications (p value 0.000). The dominant variable is maternal age with an OR value of 5.042 (95% CI 2.782-9.132) which means that mothers who are at risk (<20 and >35 years) have a 5.04 times higher chance of giving birth to LBW babies compared to mothers who are not at risk (20-35 years)